Prevalence and correlates of functional dependence among maintenance dialysis patients. Issue 4 (2nd March 2015) - Kavanagh, Niall T.; Schiller, Brigitte; Saxena, Anjali B.; Thomas, I‐Chun; Kurella Tamura, Manjula
Abstract Functional dependence is an important determinant of longevity and quality of life. The purpose of the current study was to determine the prevalence and correlates of functional dependence among patients with end‐stage renal disease (ESRD) receiving maintenance dialysis. We enrolled 148 participants with ESRD from five clinics. Functional status, as measured by basic and instrumental activities of daily living (ADL, IADL), was ascertained by validated questionnaires. Functional dependence was defined as needing assistance in at least one of seven IADLs or at least one of four ADLs. Demographic characteristics, chronic health conditions, anthropometric measurements, and laboratories were assessed by a combination of self‐report and chart review. Cognitive function was assessed with a neurocognitive battery, and depressive symptoms were assessed by questionnaire. Mean age of the sample was 56.2 ± 14.6 years. Eighty‐seven participants (58.8%) demonstrated dependence in ADLs or IADLs, 70 (47.2%) exhibited IADL dependence alone, and 17 (11.5%) exhibited combined IADL and ADL dependence. In a multivariable‐adjusted model, stroke, cognitive impairment, and higher systolic blood pressure were independent correlates of functional dependence. We found no significant association between demographic characteristics, chronic health conditions, depressive symptoms or laboratory measurements, and functional dependence. Impairment in executive function was more strongly associated with functional dependence than memory impairment. Functional dependence is common among ESRD patients and independently associated with stroke, systolic blood pressure, and executive function impairment.